The essential work of fracture method for the characterisation of fusion bonding in 3D printed short carbon-fibre reinforced polyamide 6 thin films. (10th November 2022) - He, Qinghao; Ye, Lin; Kinloch, Anthony J.
Abstract: The fusion bonding between individual filaments of 3D printed short carbon-fibre reinforced polyamide 6 (SCF/PA6) in thin films manufactured using the fused filament fabrication (FFF) process has been studied. The thin films were deposited by an 'in-plane' mode or an 'interlayer' mode. The main characterisation technique employed was the essential work of fracture (EWF) method. Undertaking EWF tests on such thin films is shown to be a feasible and efficient way to evaluate the extent and quality of fusion bonding between individual filaments of the 3D printed SCF/PA6 composites. For example, firstly, for the 3D printed SCF/PA6 thin films it was readily evident that the extent of fusion bonding, i.e. the adhesion via molecular inter-diffusion, often termed the autohesion, between the filaments is the weakest, and the most variable, in the 3D printed SCF/PA6 thin films deposited via the interlayer mode. This was indicated by the lowest measured values of both the specific essential work of fracture, w e, and the coefficient of determination, R 2, of 19.6 kJ/m 2 and 0.05, respectively, for the interlayer printed SCF/PA6 thin films. Secondly, the quality of the 3D printed SCF/PA6 thin films deposited via the in-plane mode was significantly enhanced by the use of further compression moulding process, since the value of R 2 increased from 0.77 to 0.92. The results clearly suggest the need to improve the extent and quality of fusion bonding between individual filaments printed using the FFF process when 3D printed components are made for practical applications. Graphical abstract: Image 1